STUDI ANALISIS PENGUJIAN LOGAM BERAT PADA BADAN AIR, BIOTA DAN SEDIMEN DI PERAIRAN MUARA DAS BARITO - Sofarini, Dini; Rahman, Abdur; Ridwan, Ichsan (Bumi Lestari, 2010)
This research aimed to determine heavy metal content at water body, sediment and biota, determining plankton what overflows and parameter of water quality which not fulfill standard criterion quality of water in Estuary of Barito River. Result of research showed that heavy metal rate at body of water especially Hg (0,2753 mg/l), and Pb (0,17667 mg/l) residing at biota (Giant Prawn have accumulate by heavy metal of Hg. Pb, Cu, As, Cr6+ and Cd. Sediment residing at Estuary of Barito River have accumulate by heavy metal but still under maximum boundary which have been specified. Metal rate residing in boundary sill that is cadmium metal rate (Cd) with assess metal range average 0,5655 - 0,8891 ppm, residing in of sill which have been specified equal to 0,3 ppm. Status of water quality at station perception according to Model of STORET categorized is weight, while pursuant to Model of Environmental Quality Index ( EQI) categorized as impure territorial water.